Impact of self-care training on prediabetes prevention among UIN Jakarta employees: The Role of Public Health Pharmacy in Education and Monitoring - Barita Juliano Siregar; Almahdy A; Dedy Almasdy; Syamsudin A; Ofa Suzanti Betha; Edi Rohaedi (JSFK (Jurnal Sains Farmasi & Klinis), 2025)
Prediabetes is a preclinical condition with a high risk of progressing to type 2 diabetes. This study evaluated an eight-week self-care training program among UIN Jakarta employees, facilitated by Public Health Pharmacy and integrating Avicenna’s classical health principles with WhatsApp-based digital education. A quasi-experimental pre–post design without a control group was applied to 39 participants meeting prediabetes criteria. Clinical parameters assessed included random blood glucose (RBG), systolic blood pressure (SBP), body mass index (BMI), and waist circumference (WC), along with self-care practices using the Indonesian version of the Diabetes Self-Management Questionnaire (DSMQ). Data were analyzed using Wilcoxon signed-rank test and Cohen’s dz effect size. Significant improvements were observed in SBP (dz = -0.530), BMI (dz = -0.253), WC (dz = -0.320), and DSMQ score (dz = +0.793), while RBG showed no significant change. These findings support a culturally relevant, cost-effective model for workplace-based prediabetes prevention. In line with American Diabetes Association (ADA) 2025 Standards of Care, the approach emphasizes person-centered Diabetes Self-Management Education and Support (DSMES) and team-based support; European Society of Cardiology (ESC) 2024 guidelines align the observed SBP reduction with recommended targets after lifestyle intervention. Future programs should extend duration and adopt hybrid delivery for optimal glycemic control.